POLYGON SHAPE DATA COLLECTION SYSTEM - MAKTAR, AHMAD AMINUDDIN (2018)
Ultrasound Sensors (US) is useful in measuring the distance of an object; with multiple sensor, set data can be harvest quickly depending on distance of sensor to object. This paper mainly focus on harvesting set data of distance measuring from sensor to object whereby the object placed at the center of hexagon arrangement of ultrasonic sensor. Algorithm programmed in Arduino Mega to make sure the ultrasonic sensor firing sequentially to avoid the noise interference. Set of data collected using CoolTerm software then export as text file for processing in Matlab. The object scanned using ultrasonic represented as distance proceed with reconstruction into 3-dimensional surface object. The image resurface from the point plotted then processed until smooth image formed